Mountainous terrain coverage in mobile sensor networks. Issue 5 (1st March 2015) - Kim, Kyungjun
Abstract : The sensing field on three‐dimensional (3D) terrains that is supposed to be fully covered by deployed nodes may not be covered because of random aerial deployment. Non‐uniform coverage has a negative impact upon that their lifetime and performance get short and worse, respectively. Mobile sensor networks (MSNs) are introduced to improve a coverage problem from sensor malfunction by an obstacle or the terrestrial environment. Providing coverage in a mountainous terrain has become critical issues in MSNs. This work proposes a 3D coverage method that can consider a physical feature, such as slope, in a mountainous terrain, that is, a 3D spiral model that allows mobile sensors to move freely in spiral lines devised using the height and radius of a concaved terrain. In the proposed model, the reasonable number of sensors to be deployed and the designated sensing points achieve full coverage. This paper focuses on full coverage for which the spiral model challenges the reasonability in the number of sensors. The experimental results show that the proposed method provides improved performance in terms of coverage ratios and expected coverage time; in addition, this has higher accuracy in lower power cost and better expansibility.